1996
DOI: 10.1111/j.1540-8167.1996.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine‐Induced Ventricular Arrhythmias in Dogs with Inherited Sudden Death

Abstract: Phenylephrine increases ventricular arrhythmias in dogs with inherited sudden death via both an induction of reflex bradycardia and a direct myocardial effect. Superimposition of heightened alpha-adrenergic and vagal tone may facilitate the development of sudden death in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Data from Perticone et al (93) confirm a delayed maturation or impaired functioning of the autonomic nervous system in the first weeks of life in newborns affected by SIDS. In an established experimental model for sudden death involving conscious dogs with a healed myocardial infarction, either depressed reflex chronotropic responses during a blood pressure rise or reduced variability of heart rate (respectively, markers of reflex and tonic cardiac vagal activity) identify dogs at greater risk of developing malignant arrhythmias during a new ischemic episode (94). Moreover, activation of the renin-angiotensin-aldosterone system (RAAS) in left ventricular systolic dysfunction is a critically important determinant in the pathophysiologic processes that lead to progression of heart failure and SCD.…”
Section: Neuroendocrine Actionsmentioning
confidence: 99%
“…Data from Perticone et al (93) confirm a delayed maturation or impaired functioning of the autonomic nervous system in the first weeks of life in newborns affected by SIDS. In an established experimental model for sudden death involving conscious dogs with a healed myocardial infarction, either depressed reflex chronotropic responses during a blood pressure rise or reduced variability of heart rate (respectively, markers of reflex and tonic cardiac vagal activity) identify dogs at greater risk of developing malignant arrhythmias during a new ischemic episode (94). Moreover, activation of the renin-angiotensin-aldosterone system (RAAS) in left ventricular systolic dysfunction is a critically important determinant in the pathophysiologic processes that lead to progression of heart failure and SCD.…”
Section: Neuroendocrine Actionsmentioning
confidence: 99%
“…It is inevitable in phenotyping many disorders that the line of true delineation of normal and abnormal is blurred. We have also found that a phenylephrine challenge can be used to identify affected dogs at earlier ages 2 …”
Section: Discussionmentioning
confidence: 86%
“…We have also found that a phenylephrine challenge can be used to identify affected dogs at earlier ages. 2 Another difficulty in identifying VA by routine ECG is the dependence of behavior in exposing the arrhythmia, particularly in mildly to moderately affected dogs. Holter monitoring provides an opportunity to observe VA during rest or sleep that might not be present during the excitement of ECG examination.…”
Section: Pattern Of Inheritance: Dependence On Correct Phenotype Idenmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the most prominent effect was from the fentanyl, based on the doses used, the heart rate was slowed because of the increased vagal tone caused by the narcotic. 16,17 Our second contemplation concerned the underlying mechanism of the atrial fibrillation and the use of the dominant frequency and spectral entropy to determine whether a frequency or organizational gradient existed between the left and right atrium in the German Shepherd Dogs under these conditions. Therefore, the purpose of the study reported here was to determine whether atrial fibrillation could be induced in these dogs as an open-thorax model that would permit future studies (eg, epicardial mapping) of arrhythmia initiation and propagation and to determine the dominant frequency and spectral entropy gradients across the atria during atrial fibrillation.…”
mentioning
confidence: 99%